Arable weed vegetation and germination traits of frequent weeds in Kosovo - Mehmeti, Arben; Justus Liebig University Giessen (My University, 2009)
Research on changes in Europe s arable weed flora and vegetation, which resulted from changes in agricultural practices, has been conducted since about 1970, but has concentrated on Central and Northern Europe. Thus, only few data on changes in the arable weed flora and vegetation have been available from Southern Europe including the Republic of Kosovo, located in the centre of the Balkan Peninsula, Europe s major hotspot of biodiversity. In general, Kosovo is known for its rich flora and vegetation. However, the knowledge on Kosovo s flora and vegetation is still incomplete or might be outdated due to pronounced land-use changes in the last two decades. With respect to the arable weed flora and vegetation of Kosovo, no comprehensive research has been conducted since about 1980 and is thus of interest from a vegetation and landscape ecological perspective and the perspective of biodiversity conservation. Moreover, knowledge on Kosovo s arable weed flora and vegetation and on weed species traits is valuable from an agronomic perspective, since arable production is among the region s main economic activities contributing to the gross domestic product.Against this background, empirical and experimental studies conducted in this thesis (i) contribute to the ongoing floristic mapping of Kosovo, (ii) provide a reference database for future studies on land-use change and its effects on the regional arable weed flora and vegetation, (iii) provide information on the relationships between the vegetation of the arable land and both environmental features and agricultural management measures, (iv) elucidate within-region differentiations of weed species frequencies, cover and germination characteristics, and (iv) analyse region-specific germination traits of three frequent weed species, namely A. retroflexus, E. crus-galli and D. stramonium.Based on the results of an empirical study in 432 cultivated arable fields in 2006, today s arable weed flora and vegetation of Kosovo is characterised by a low alpha-species richness with mean species numbers between 8 (in vegetables) and 10 (in winter wheat) per 25 m², the predominance of few nitrophilic and often herbicide-resistant species at the plot and regional scale, a low cover (at the plot scale) and low occurrence frequencies (at the regional scale) of the larger fraction of weed species (187 of 235 species), decreased frequencies of some arable weeds s. str. compared to the situation around 30 years ago, a nearly total lack of differences in species composition due to site conditions (e.g. altitude above sea level, soil base-richness, soil moisture), marginal differences in the weed flora between two sub-regions of Kosovo that differ in climate and land use, and pronounced differences in species composition between fields that differ in crops (summer vs. winter crops) and weed control (chemical vs. mechanical measures).As it may be concluded from an empirical study conducted in 41 recently abandoned arable fields in 2007, the alpha-species richness (in average 18.8 species per 25 m²) and the frequencies of arable weed species are higher in recently abandoned than in cultivated arable fields. This result indicates a potential for future development of species rich weed communities, provided by the soil seedbanks of the arable land.Based on the results of a climate chamber experiment and a field experiment conducted in 2007, the germination behaviour of three problematic arable weeds of Kosovo, namely Amaranthus retroflexus, Echinochloa crus-galli and Datura stramonium, is found to be as follows: The temperature-dependent germination behaviour is species-specific and, for one species, the germination behaviour differs for seeds originating from different provenances within Kosovo, indicating ecological adaptation at the population level.The results of the empirical and experimental studies are discussed against the need to develop and implement sustainable agricultural systems considering the multifunctionality of agriculture. Moreover, shortcomings in the availability of spatially-explicit databases on the geometry and pattern of Kosovo s agricultural land parcels and land use types are discussed in the context of relationships between biodiversity and landscape structure. Finally, suggestions for future research in the arable land of Kosovo and on traits of the region s problematic weed species are presented.

In Europa seit etwa 1970 durchgeführte Untersuchungen belegen Änderungen in der Ackerflora und -vegetation als Folgen geänderter landwirtschaftlicher Praxis. Die meisten Arbeiten zu diesem Themenbereich erfolgten bislang in Mittel- und Nordeuropa, so dass entsprechende Kenntnisse aus Südeuropa nur vereinzelt vorliegen. Dies gilt auch für die als Hotspot der Biodiversität Europas bezeichnete Balkanhalbinsel, in deren Zentrum die Republik Kosovo liegt. Allgemein ist Kosovo für seine reichhaltige Flora und Vegetation bekannt, jedoch sind die Kenntnisse unvollständig oder könnten aufgrund ausgeprägter Landnutzungsänderungen, die seit zwei Jahrzehnten zu verzeichnen sind, veraltet sein. Zur Ackerflora und -vegetation des Kosovos liegen seit etwa 1980 keine umfassenden Arbeiten vor. Entsprechende Untersuchungen sind daher aus vegetations- und landschaftsökologischer Sicht und aus der Sicht des Biodiversitätschutzes von Bedeutung. Darüber hinaus sind das Wissen um die Ackerflora und -vegetation sowie Kenntnisse zu Arteigenschaften von Ackerunkräutern des Kosovos von agronomischem Interesse, da die landwirtschaftliche Produktion für das Bruttoinlandsprodukt der Republik Kosovo von größter Bedeutung ist.Vor diesem Hintergrund wurden im Rahmen der vorliegenden Arbeit empirische und experimentelle Untersuchungen durchgeführt, die (i) zur laufenden floristischen Kartierung des Kosovos beitragen, (ii) eine Datengrundlage für künftige Untersuchungen zu Folgen geänderter Landnutzung auf die regionale Ackerflora und vegetation bereitstellen, (iii) Informationen zu Beziehungen zwischen Vegetation, Standort und Ackernutzung geben, (iv) Erkenntnisse zu innerregionalen Unterschieden der Häufigkeiten, Abundanzen und Keimungseigenschaften von Unkräutern liefern und (v) das regionenspezifische Keimungsverhalten der drei häufigen Ackerunkräuter Amaranthus retrofloexus, Echinochloa crus-galli und Datura stramonium untersuchen.Auf der Grundlage der Ergebnisse empirischer Erhebungen in 432 bestellten Ackerschlägen im Jahr 2006, ist die aktuelle Ackerflora und -vegetation des Kosovos durch einen niedrigen alpha-Artenreichtum mit im Mittel 8 (Gemüseanbau) bis 10 (Winterweizen) Arten pro 25 m², das Vorherrschen weniger nitrophytischer und oft herbizidresistenter Arten auf plot- und Landschafts-Ebene, niedrige Deckungsgrade (auf plot-Ebene) und geringe Häufigkeiten (auf Landschafts-Ebene) der meisten Ackerunkräuter (187 von 235 Arten), im Vergleich zur Situation vor etwa 30 Jahren heute geringere Häufigkeiten einiger Ackerunkräuter im engeren Sinne, fast vollständiges Fehlen von Unterschieden in der Artenzusammensetzung in Abhängigkeit von Standorteigenschaften (z.B. geographische Höhe, Basenreichtum und Wasserversorgung der Böden), nur geringe Unterschiede in der Unkrautflora zweier Teilräume des Kosovos, die sich hinsichtlich Klima und Landnutzung unterscheiden, sowie ausgeprägte Unterschiede in der Artenzusammensetzung in Abhängigkeit von den angebauten Kulturen (Sommerungen vs. Winterungen) und der Form der Unkrautkontrolle (chemische vs. mechanische Kontrolle) gekennzeichnet.Aus empirischen Erhebungen in 41 jungen Ackerbrachen im Jahr 2007 wird geschlossen, dass der alpha-Artenreichtum (durchschnittlich 18.8 Arten pro 25 m²) und die Häufigkeiten von Ackerunkräutern in jungen Ackerbrachen höher als in bestellten Ackerflächen sind. Dies deutet auf ein durch die Bodensamenbank des Ackerlands gegebenes Potenzial zur künftigen Entwicklung artenreicher Ackerunkrautgemeinschaften hin.Auf der Grundlage der Ergebnisse zweier im Jahr 2007 durchgeführter Experimente, eines Klimaschank-Experiments und eines Freilandexperiments, wird das Keimungsverhalten der drei im Kosovo problematischen Ackerunkräuter Amaranthus retroflexus, Echinochloa crus-galli and Datura stramonium wie folgt gekennzeichnet: Das temperaturabhängige Keimungsverhalten ist artspezifisch, und auf Artebene unterscheidet sich das Keimungsverhalten von Samen, die aus zwei unterschiedlichen Teilräumen des Kosovos stammen. Dies deutet auf eine ökologische Anpassung auf Populations-Ebene hin.Die Ergebnisse der empirischen und experimentellen Untersuchungen werden vor dem Hintergrund der Notwendigkeit diskutiert, unter Berücksichtigung der Multifunktionalität der Landwirtschaft nachhaltige landwirtschaftliche Nutzungssysteme zu entwickeln und umzusetzen. Darüber hinaus werden im Kontext von Beziehungen zwischen Biodiversität und Landschaftsstruktur Defizite in der Verfügbarkeit räumlich expliziter Daten zur Geometrie und zu den Raummustern der landwirtschaftlichen Schläge des Kosovos und der dort implementierten Landnutzungen diskutiert. Schließlich werden Empfehlungen für künftige Forschungsarbeiten im Ackerland des Kosovos und zu den Eigenschaften der Problemunkräuter dieses Raumes gegeben.
Segetalvegetation und Keimungseigenschaften häufiger Unkräuter im Kosovo
Keywords: Segetalvegetation; Ackerunkraut; Ökologie; Naturschutz; Balkanhalbinsel; Arable vegetation; arable weed; ecology; nature conservation; Balkan Peninsula; ddc:630